Intratemporal nonseparability between housing and nondurable consumption: evidence from reinvestment in housing stock - Natalia Khorunzhina (Center for Economic Studies and ifo Institute (CESifo), 2019)
Using the data on maintenance expenditures and self-assessed house value, I separate the measure of individual housing stock and house prices, and use these data for testing whether nondurable consumption and housing are characterized by intratemporal nonseparability in households' preferences. I find evidence in favor of intratemporal dependence between total nondurable consumption and housing. I reach a similar conclusion for some separate consumption categories, such as food and utility services. My findings also indicate households are more willing to substitute housing and nondurable consumption within a period than to substitute composite consumption bundles over different time periods.
Keywords: C51; D12; D13; E21; R21; 330; intratemporal nonseparability; housing; nondurable consumption